Dual high-Q Fano resonances metasurfaces excited by asymmetric dielectric rods for refractive index sensing - Wang Tianyu; Liu Siqi; Zhang Jiahang; Xu Liang; Yang Mingyu; Ma Ding; Jiang Sijia; Jiao Qingbin; Tan Xin (Nanophotonics, 2024)
The metasurface refractive index sensor has a high degree of tunability and flexibility, providing excellent performance for high precision refractive index sensing applications. The metasurface absorber with metallic structure has been hindered in further sensor applications due to the inherent Ohmic loss of the metallic material. In this study, a dual nanorod metasurface structure based on semiconductor Si was designed, introducing a symmetry-breaking structure to excite dual ultra-narrow q-BIC resonance peaks with Fano line shapes. Both peaks are located in the near-infrared region, and multipole analysis shows that this strong field enhancement effect is induced by a magnetic dipole. Experimental results demonstrate the potential of this sensor to provide dual-channel detection while achieving high sensitivity and high Q-factor. We believe that this device exhibits outstanding performance and high practicality, providing a reference for the development and application of biological and environmental sensors.